PENGARUH PEMAHAMANA HALAL DAN HAMBATAN ADMINISTRASI TERHADAP KESIAPAN PELAKU UMKM DI GATSU FOOD SQUARE BANJARMASIN DALAM PROSES SERTIFIKASI HALAL - Lisda Aisyah (Fakultas Ekonomi dan Bisnis IAI Darussalam Martapura, 2026)
The background of this study is the low level of readiness of some Micro, Small, and Medium Enterprises (MSMEs) in Gatsu Food Square Banjarmasin in participating in the halal certification process, even though the obligation of halal certification continues to be pushed by the government. This condition is thought to be influenced by the unequal level of halal understanding among MSMEs and the existence of complex administrative obstacles, this is what can make it difficult for business actors to carry out the halal certification process. Therefore, this study aims to analyze the influence of halal understanding and administrative obstacles on the readiness of MSMEs in Gatsu Food Square Banjarmasin in the halal certification process both simultaneously and partially. This study uses a quantitative method using a data collection method in the form of distributing questionnaires (questionnaires) with a saturated sampling technique involving 30 respondents. The results obtained were then analyzed using SPSS V.25. In the study, both simultaneously (F-test) and partially (T-test), the two variables between halal understanding (X1) and administrative obstacles (X2) obtained results that both did not have a simultaneous and partial effect on the readiness of MSMEs in Gatsu Food Square Banjarmasin in the halal certification process. The variables of halal understanding and administrative barriers only explain 16.3% of the MSME readiness variable, with the remaining 83.7% being influenced by other variables.